Production and Application of Lactobacillus plantarum IBL-2 Bacteriocins as Meat Product Biopreservatives - Marlia Singgih Wibowo; Isra Muzakiyah; Betty Nurhayati; Tjokorde Armina Padmasawitri; Yantyati Widiastuti; Tutus Gusdinar (Indonesian Food and Nutrition Progress, 2017)
Biopreservation is one of the alternatives to obtain safe food products. The produced bacteriocin by Lactic Acid Bacteria (LAB) is potential as biopreservatives, which is safe for consumption, since it was a protein degradable by proteolytic enzymes. This study aimed to optimize bacteriocin production from L. plantarum IBL-2 and to evaluate the effectiveness of bacteriocins in reducing the number of total plate count and Salmonella typhimurium in ground beef. Bacteriocin was produced through fermentation of L. plantarum IBL-2, under various conditions to yield the compound with the best antimicrobial activity. The total number of bacteria in ground beef after the addition of L. plantarum IBL-2 fermentation supernatant was determined. The result was compared with the sample without preservatives (control), and sample added with commercial Nissin. All three samples of ground beef were spiked with S. typhimurium and incubated for 0, 2, 6, 8, 12, 14 days at a temperature of 4-10 ° C. Total Plate Count (TPC) method was utilized to determine the number of bacteria in the samples. The fermentation process resulted in bacteriocin with the strongest antimicrobial activity when using low molecular weight liquid medium (LMWLM), followed by a series of refining process. From day 0-14, the number of S. typhimurium, in sample added with L. plantarum IBL-2 fermentation supernatant, was lower than control and sample added with Nissin. The most optimal antimicrobial activity of bacteriocin was obtained using LMWLM as fermentation media, and using a series of refining process consist of bacteriocin supernatant evaporation, membrane ultrafiltration, and gradual fractionation using 80% ammonium sulphate. Bacteriocin from L. plantarum IBL-2 showed antimicrobial activity against S. typhimurium.